Nodule-specific modulation of glutamine synthetase in transgenic medicago truncatula leads to inverse alterations in asparagine synthetase expression - Carvalho, Helena (2020)
Transgenic Medicago truncatula plants were produced harboring chimeric gene constructs of the glutamine synthetase (GS) cDNA clones (MtGS1a or MtGS1b) fused in sense or antisense orientation to the nodule-specific leghemoglobin promoter Mtlb1. A series of transgenic plants were obtained showing a 2- to 4-fold alteration in nodule GS activity when compared with control plants. Western and northern analyses revealed that the increased or decreased levels of GS activity correlate with the amount of cytosolic GS polypeptides and transcripts present in the nodule extracts. An analysis of the isoenzyme composition showed that the increased or decreased levels of GS activity were attributable to major changes in the homo-octameric isoenzyme GS1a. Nodules of plants transformed with antisense GS constructs showed an increase in the levels of both asparagine synthetase (AS) polypeptides and transcripts when compared with untransformed control plants, whereas the sense GS transformants showed decreased AS transcript levels but polypeptide levels similar to control plants. The polypeptide abundance of other nitrogen metabolic enzymes NADH-glutamic acid synthase and aspartic acid aminotransferase as well as those of major carbon metabolic enzymes phosphoenolpyruvate carboxylase, carbonic anhydrase, and sucrose synthase were not affected by the GS-gene manipulations. Increased levels of AS polypeptides and transcripts were also transiently observed in nodules by inhibiting GS activity with phosphinothricin. Taken together, the results presented here suggest that GS activity negatively regulates the level of AS in root nodules of M. truncatula. The potential role of AS in assimilating ammonium when GS becomes limiting is discussed.